Connecting the Dots in Digital Labor Marketplace: A Bibliometric Review of Global Gig Dynamics - Praveen Chaudhary; Pratibha Kiran Niroula (Research Synergy Foundation, 2024)
In the multi-faceted tapestry of modern employment, the burgeoning global gig economy represents a seismic shift, encapsulating technological advancements that have reshaped contemporary work structures. This unprecedented rise has triggered a paradigm shift in labor structures, provoking intense debates on the fundamental redefinition of traditional employment models in the global economic sphere. This study addressed the imperative need to comprehend and contextualize these dynamics, driven by technology and characterized by short-term, digitally facilitated work engagements. Among the transformative sway of the gig economy, this study endeavors a comprehensive bibliometric review, shedding light on trends shaping the dynamics. Employing the Dimensions Digital Science database, our methodology involved a meticulous search strategy, resulting in a collection of relevant scholarly publications. We conducted rigorous data cleaning and validation and applied bibliometric analysis using Biblioshiny (Bibliometrics) in RStudio. The findings reveal a marked surge in gig economy publications, emancipating the growing scholarly interest. Thematic analysis emphasized emerging trends such as digital platform work, regulatory efficiencies, and socioeconomics as focal areas. This study provides a holistic overview of the scholarly output on gig economy literature, offering a comprehensive understanding of its evolution and complexities. This serves as a foundational resource for all stakeholders, guiding further studies and facilitating evidenced decision-making in the ever-evolving landscape. By synthesizing current knowledge on digital labor marketplace dynamics and pinpointing emerging trends in the creative gig economy, this review informs future research agendas and fosters a deeper understanding.